Perilaku Jual Beli Di Kalangan Pedagang Kaki Lima Dalam Perspektif Etika Bisnis Islam - Darmawati Darmawati (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2012)
Islamic business ethics teach people to have a good behavior and to avoid the bad ones. It is based on Islamic values. Islam has a role about the weights of goods. It has been written in Al-Qur’an and hadits. Islam suggests people do business in a right way; because Islam deals with productivity in trade. In trade, both the producers and the consumers will have benefits from the trade. A good purchace and sale activity involve an honesty; in the right or wrong way. In Islamic business law, the concept of muamalah is mubah, unless it is done based on Al-Qur’an and Sunnah, without coercion, benefits-based consideration, avoiding bad effects, and fair